Synthesis of Isoxazolines and Isoxazoles Inspired by Fipronil - Miller, Daniel K.; Bailey, Christopher A.; Sammelson, Robert E. (Synthesis, 2015)
Phenylpyrazoles (or arylpyrazoles) are known to be extremely potent as noncompetitive inhibitors of the GABA-gated chloride channel on the GABA receptor. This project involves the synthesis of novel isoxazole and isoxazoline heterocycles that have similar structural features to the commercially used phenylpyrazole, fipronil. Synthesis of the appropriately substituted styrenes and phenylacetylenes is followed by 1,3-dipolar cycloaddition reaction with several aliphatic nitrile oxides, which are prepared in situ from aldoximes with bleach. Relative reaction rates were determined for these specialized alkene and alkyne dipolarophiles.
Keywords: oximes; nitrile oxides; styrenes; substituted phenylacetylenes; 1,3-dipolar cycloaddition